The effects of propranolol and chlorisondamine on amphetamine hyperthermic action on brown adipose tissue in lean and obese zucker rats - Abdul Karim, Mohamad Nordin (Malaysian Nuclear Agency, 1989)
Thermogenic capacity of brown adipose tissue was measured by [3H] GDP binding on the mitochondrial preparation of the tissue. Obese Zucker Rats are found to be more sensitive to amphetamine compared to the lean genotype. Amphetamine stimulation involves β - receptors and is centrally controlled. Increase in thermogenesis by amphetamine does not involve stimulation of the mitochondrial enzymic activity.